P68 Diagnostic accuracy of endometrial biopsy in endometrial carcinoma grading, correlated to the amount of tissue. (1st November 2019) - Hulsman, AMC; Reijnen, C; Bulten, J; Kusters, HVN; van de Vijver, K; Santacana, M; Colas, E; Mancebo, G; Reques, A; Gil-Moreno, A; Trovik, J; Krakstad, C; et al.
Abstract : Introduction/Background: The diagnostic accuracy of endometrial biopsy has been related to the amount of tissue. In endometrial cancer (EC) there is only moderate agreement on tumor grade between preoperative endometrial sampling and final diagnosis with the lowest agreement for grade 2 carcinoma. Since the amount of preoperative endometrial tumor tissue has not yet been related to the degree of discordance, we aim to determine this relation with regard to final tumor type and grade. Methodology: Within the European Network for Individualized Treatment of Endometrial Cancer (ENITEC), 582 preoperative endometrial biopsy samples of EC patients were retrospectively collected and classified into low-grade (grade 1–2) and high-grade carcinoma (grade 3). The endometrial tissue surface was digitally calculated using ImageJ software and the correlation between the amount of tissue and concordance of diagnosis was calculated. Results: Agreement on tumor grade between preoperative endometrial sampling and final diagnosis was 62.5%. Up- or downgrading was found in respectively 27.1% and 10.3%. Clinically relevant up- or downgrading was found in respectively 7.8% and 27% of the cases. Premalignant endometrial tissue contained less endometrium compared to malignant endometrium (4.4 vs. 19.3 mm 2, p=0.03). Serous EC contained less endometrial tissue compared with grade 1–3 endometrioid EC (13.0 vs. 19.1 mm 2, p=0.017). The median endometrial tissue surfaces of grade 1-3 did not significantly differ from each other (18.7 vs. 19.8 vs. 24.1 mm 2 ). Samples with a discordant diagnosis consisted of significantly more endometrial tissue compared to the concordant group (p=0.018). Conclusion: Based on postoperative diagnosis, there is no difference in the amount of endometrial tissue between the different endometrial grades. However, there is a tendency to underestimate a sample with less and overestimate a sample with more endometrial tissue. Awareness is especially needed, in serous EC with in general less tissue. Disclosure: Nothing to disclose.